Are 2 Radiographic Views As Good as 3 Views to Diagnose Ankle Fractures in Children and Adolescents?. Issue 9 (9th September 2022) - Abouassaly, Marcel; Blumetti, Francesco Camara; Gauthier, Luke; Willis, Ross Baxter; Kontio, Ken; Highmore, Kerri; Abdeen, Nishard; Plint, Amy Catherine; Tse, Sandy; Barrowman, Nick; Moroz, Paul John
Abstract : Objectives: Ankle radiographs are among the most commonly obtained trauma images in the pediatric population, with the standard 3 views (AP/mortise [M]/lateral [L]) routinely ordered in the emergency department. The purpose of this study was to compare the diagnostic accuracy, sensitivity, and specificity of sets of 2 views (AP/L or M/L) with the standard 3 views. Methods: One hundred twenty sets of ankle radiographs of skeletally immature patients obtained in the emergency department of a level 1 pediatric trauma center were used. These included sets with and without fractures. Sets of 3 and 2 views were reviewed by pairs of pediatric-trained orthopedic surgeons, radiologists, and emergency physicians. Each completed 3 randomized viewing sessions where all possible combinations for each set of radiographs were reviewed. Diagnoses for the 3 sets of views were compared for accuracy, sensitivity, and specificity. Results: Overall accuracy, sensitivity, and specificity for all reviewers were as follows: AP/M/L 74%, 94%, and 90%, AP/L 71%, 90%, and 94%, as well as M/L 69%, 90%, and 91%. P values for accuracy, sensitivity, and specificity of AP/L and M/L compared with 3 views were 0.34, 0.04, and 0.52, as well as 0.04, 0.004, and 1.00, respectively. Conclusions: In skeletally immature patients, statistically significant differences in accuracy were obtained when comparing the standard 3 AP/M/L views with more limited M/L views, suggesting that this set of 2 views is not as accurate. Differences in sensitivity of limited views were also statistically significant. Conversely, differences in accuracy between the standard 3 views and AP/Lateral views were not statistically significant. While more limited AP/L views may be comparable in accuracy and specificity and lead to dramatically decreased radiation and costs, this can be at the expense of less diagnostic sensitivity and increased risk of misdiagnosing or missing certain fractures. Level of Evidence: Level III